2019
DOI: 10.1093/jamia/ocz026
|View full text |Cite
|
Sign up to set email alerts
|

Role of provider encouragement on patient engagement via online portals

Abstract: Objective The study sought to examine whether provider encouragement is associated with improvements in engaging patients with their healthcare processes using online portals. Materials and Methods Using the Health Information National Trends Survey 2017 (N = 2, 670), we conducted an exploratory factor analysis with varimax orthogonal rotation and derived 3 outcome variables on patient engagement: (1) information access score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…OMR feature usage patterns (i.e., viewing results or secure communication) among different population segments were associated with encouragement. Prior research qualitatively observed similar findings, 19 although our study adopted a different methodological and clinically focused approach. Similar effects of encouragement were noted among CVMD patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…OMR feature usage patterns (i.e., viewing results or secure communication) among different population segments were associated with encouragement. Prior research qualitatively observed similar findings, 19 although our study adopted a different methodological and clinically focused approach. Similar effects of encouragement were noted among CVMD patients.…”
Section: Discussionsupporting
confidence: 78%
“…16 17 Only 39% of patients reported to have discussed health information technology use with their providers 18 and 59% reported no provider encouragement for OMR use. 19…”
Section: Background and Significancementioning
confidence: 99%
“…One promising action to reduce such disparities in portal use is to aim for universal access to health information technology tools and to become aware of users' health literacy levels and preferred ways of communicating with the providers [66]. While provider encouragement is one of the factors associated with increased access and use of patient portals [67][68][69][70], referrals vary by patient race, socioeconomic status, and providers' personal beliefs about the benefits of patient portal use, contributing significantly to access disparities [22,71]. Targeting providers with additional patient portal referral training could be an effective strategy for increasing patient portal adoption among cancer patients, as demonstrated in studies of other patient populations [72][73][74].…”
Section: Principal Findingsmentioning
confidence: 99%
“…This finding supports the idea that digital health empowers patients to be active participants [ 9 - 11 ]. However, the changing role of patients may have required physicians to more actively encourage their patients to engage in digital health [ 73 ]. Patients also need a variety of skills, such as digital health literacy, to play an independent role [ 74 ].…”
Section: Discussionmentioning
confidence: 99%